2008
DOI: 10.1007/s10562-008-9611-5
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel Synthesis of MoO3/SiO2 Composite for Catalytic Application in Condensation of Anisole with Paraformaldehyde

Abstract: MoO 3 /SiO 2 composite with varying amounts of MoO 3 loading (1-20 wt.%) were prepared by sol-gel method and calcined at 500°C. These catalysts were employed for the liquid phase condensation of anisole with paraformaldehyde. All the catalysts were characterized by N 2 sorption, XRD, and NH 3 -TPD. The activities of synthesized MoO 3 /SiO 2 catalysts were compared with p-toluene sulfonic acid (p-TSA), the most frequently used catalyst for the condensation reactions, and with a supported metal oxide (WO x /ZrO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Their insolubility in response solvents renders them effectively detachable from the response blend, which thus makes the item separation arrange easy. Outstandingly, the MMONs are better as far as their catalytic movement than the individual metal oxides in different responses as a result of their improved surface area [37][38][39][40][41]. Consequently, in perspective on present day catalytic science, MMONs represents a standout amongst the most vital and generally utilized materials in catalysis science.…”
Section: Introductionmentioning
confidence: 99%
“…Their insolubility in response solvents renders them effectively detachable from the response blend, which thus makes the item separation arrange easy. Outstandingly, the MMONs are better as far as their catalytic movement than the individual metal oxides in different responses as a result of their improved surface area [37][38][39][40][41]. Consequently, in perspective on present day catalytic science, MMONs represents a standout amongst the most vital and generally utilized materials in catalysis science.…”
Section: Introductionmentioning
confidence: 99%
“…The SA of the SiO 2 structure, for Mo 2 C/SiO 2 -SG was not determined; however, it was previously confirmed that upon a 20 wt % Mo loading, the BET surface area drops from 450 to 86 m 2 /g. 24 Probing CO 2 Activation on Mo 2 C by Temperature Programmed Reaction of CO 2 . The activation of thermodynamically stable CO 2 is the key step in the RWGS reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Synthesis of Mo 2 C/SiO 2 -SG. The sol−gel (SG) method was adapted from Amrute et al 24 In short, 3.07 g of ammonium heptamolybdate was dissolved in 100 mL of hot distilled water, targeting a final loading of 20 wt % Mo on SiO 2 . The AHM solution was added dropwise under stirring to a solution of 37.16 mL of tetraethyl orthosilicate (TEOS, Sigma-Aldrich, 99.99%) in 20 mL of 2-propanol (anhydrous, Sigma-Aldrich, 99.5%), followed by a 3 h aging step while continuously stirring.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In fact, this type of catalyst is known to be active in different reactions but its activity is always related to the nature of the active phase, which itself depends on the active species present on the surface which in turn varies according to the molybdenum loading, the preparation method and also the nature of the support [23]. In this sense, Belatel et al [5] pressure in a flow fixed-bed reactor.…”
Section: Introductionmentioning
confidence: 99%